Exploring the synergy of blockchain technology and low-carbon innovation for enterprise sustainability for unlocking a sustainable energy - A., ZiYa; Guo, XiaoChuan (Frontiers in Energy Research, 2023)
Along with further implementation of the policy strategy of carbon peaking and carbon neutralization in our country, the development idea of realizing the “dual carbon” goal with emphasis on environmental protection and low-carbon technology development has been preliminary established. At present, Chinese energy enterprises urgently need to break the dilemma between system and efficiency through technological innovation, so as to achieve the goal of sustainable development. Based on the legitimacy theory and stakeholder theory, this paper discusses the internal mechanism and boundary conditions of low-carbon technology innovation affecting the sustainable development of energy enterprises. Based on the data of listed Chinese energy companies from 2015 to 2021, the empirical study found that the level of low-carbon technology innovation of energy enterprises has an inverted U-shaped positive impact on their sustainable development performance, and the dual legitimacy (political legitimacy, market legitimacy) plays a part of the intermediary role. The degree of market competition positively moderates the relationship between low-carbon technology innovation and political legitimacy, and positively moderates the mediating effect of political legitimacy between low-carbon technology innovation and sustainable development performance. However, the degree of market competition has no significant moderating effect on the relationship between low-carbon technology innovation and market legitimacy, nor can it significantly regulate the mediating effect of market legitimacy. The constraint strength of “dual carbon” targets positively moderates the relationship between low-carbon technology innovation and political legitimacy, and positively moderates the mediating effect of market legitimacy between low-carbon technology innovation and sustainable development performance. On the contrary, the “dual carbon” target constraint intensity negatively moderates the relationship between low-carbon technology innovation and market legitimacy, and negatively moderates the mediating effect of market legitimacy. This article not only provides a new perspective for the integration of low-carbon innovation and legitimacy theory, but also provides theoretical reference and guidance for the practice of low-carbon technology innovation in energy enterprises.